IMPLEMENTASI ALGORITMA GENETIKA PADA PENJADWALAN SISTEM INFORMASI XYZ TV - Asmarajati, Dian; Asnawi, Muhamad Fuat; Akmal, Rizaq Dian (Riau Journal Of Computer Science, 2020)
Scheduling is a method used to determine the resources or duration of work time needed to carry out a series of work activities. The purpose of scheduling is to complete a job regularly, run smoothly and according to plan. The problem that is being experienced on XYZ TV is the making of show schedules that still use Ms. Excel and frequent errors in making a schedule, In addition, also making a schedule that still uses Ms. Excel can result in a schedule of events that can later collide with other event schedules. This makes the agency takes a long time in making the show schedule. In the process of making a scheduling system, we need an algorithm that can find the best combination of genetic algorithms which is a very appropriate algorithm used to solve complex optimization problems that are difficult to do by conventional methods. For this purpose, a scheduling application is made using genetic algorithms to schedule shows on XYZ TV. So, in this case the scheduling application can make it easier for the agency in making the schedule of shows automatically